Actual influence cost estimation of water resources in coal mining and utilization in China - El-Shikha, D. (2020)
This study, the first of its kind for guayule, compares the metrics of energy consumption, lifecycle environmental impacts and irrigation water productivity. Drip irrigation showed a more efficient use of the applied water by generating higher rubber (46%) and bagasse (dry matter) yields (49%) compared to flood irrigation. On the other hand, drip irrigation showed 13% higher energy consumption than flood because of the additional burdens of water pumping. Experimental field operations were the central contributor to energy consumption in both irrigation methods. By separating a crucial stage of guayule production, namely irrigation, connections emerge between various key parameters in the two irrigation methods; accordingly, the outcomes from the evaluation of these two irrigation systems can assist with decision-making in the lifecycle framework of guayule rubber production.